IMPLIKASI DUKUNGAN PASANGAN TERHADAP PRESTASI AKADEMIK MAHASISWA MENIKAH: STUDI KASUS PADA MAHASISWA STDIIS JEMBER - Wijayanto, Wahyu (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study examines the impact of marriage on student academic achievement at STDI Imam Syafi'i Jember, focusing on spousal support in balancing home and academic life. Using a qualitative approach, this study explores the adaptation strategies of married students, as well as providing contextual insights and recommendations for support policies for married students in achieving optimal achievement. The method used was a case study to understand the experiences of married students at STDI Imam Syafi'i Jember. Respondents were active married students who were willing to participate. Data were collected through interviews to explore the influence of spousal support on academic achievement, focusing on the complex social phenomena in their lives.The results revealed that spouses' attitudes towards the dual roles of married students had a significant effect on emotional and practical support, which helped them face academic challenges. This support increases motivation to study, time management, and emotional well-being, which contributes to better academic performance, including an increase in Grade Point Average (GPA) and the ability to manage responsibilities. This study shows that spousal support, both emotional and practical, plays an important role in the academic performance of married students, so campuses need to provide appropriate support programs.